2015
DOI: 10.1186/s12974-015-0429-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sex-specific effects of apolipoprotein E on severity of EAE and MS

Abstract: BackgroundDespite pleiotropic immunomodulatory effects of apolipoprotein E (apoE) in vitro, its effects on the clinical course of experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis (MS) are still controversial. As sex hormones modify immunomodulatory apoE functions, they may explain contentious findings. This study aimed to investigate sex-specific effects of apoE on disease course of EAE and MS.MethodsMOG35-55 induced EAE in female and male apoE-deficient mice was assessed clinically and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Nevertheless, results are mixed, and whether these relations are causal or secondary to the disease process, treatment regimens or other confounding factors remain uncertain. Complex interactions between cholesterol metabolism and sex steroids are well-known (3) and may modulate the clinical activity of experimental autoimmune encephalomyelitis (EAE), the animal model for MS (4, 5). Therefore, we hypothesized that the putative associations between lipoprotein metabolism and the severity of MS could be modulated by sex hormone exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, results are mixed, and whether these relations are causal or secondary to the disease process, treatment regimens or other confounding factors remain uncertain. Complex interactions between cholesterol metabolism and sex steroids are well-known (3) and may modulate the clinical activity of experimental autoimmune encephalomyelitis (EAE), the animal model for MS (4, 5). Therefore, we hypothesized that the putative associations between lipoprotein metabolism and the severity of MS could be modulated by sex hormone exposure.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth noting that the association of the HLA genetic burden score reported by Isobe et al 14 was also not replicated in our larger German genetics cohort. 36 Regarding the role of APOE in MS course, genetic association results have overall been largely contradictory, [15][16][17][18][19][20] suggesting that the functional APOE variants rs429358 and rs7412 do not play a major role in defining MS severity. Along these lines, our current study may support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…However, results have been contradictory. [15][16][17][18][19][20] Most studies have investigated these factors in the context of long-term disease progression. 8,16,18 The role of any of these factors in early disease progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, the concept of MS pathogenesis was profoundly influenced by research conducted in experimental autoimmune encephalomyelitis (EAE). These animal models mimic many pathological aspects and all clinical forms of MS [ 6 , 7 , 8 ]. This has led many authors to suggest that MS has a primary autoimmune etiology.…”
Section: An Overview Of Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The Mailleux group also reported that in EAE, LDL receptor deficiency attenuates the severity of the disease in females (not in males) mice, through the induction of ApoE [ 65 ]. Interestingly, other authors have found that, in ApoE knock-out mice, ApoE deficiency increases EAE severity only in female animals [ 8 ]. These findings suggest interactions between sex steroids and cholesterol metabolism in the development of CNS lesions and severity of the disease.…”
Section: Genesis and Repair Of Ms Lesionsmentioning
confidence: 99%